Gorgias’ Revising of Ancient Epistemology: on Non-Being by Gorgias and its Paraphrases - Volf, Marina (Revista Archai, 2021)
The philosophical nature of the two versions of paraphrasing the Gorgias’ treatise On Non-Being — the skeptical version by Sextus Empiricus and the peripatetic version by an anonymous author — are discussed. The paper gives a comparative analysis of the arguments upheld by the informants enunciating Gorgias’ thoughts, demonstrates the range of philosophical problems, which Gorgias considered, judging by the reports of his speech, and shows how both versions add to and clarify each other in terms of philosophical issues. The work provides insights as to how Gorgias modernizes and transforms the initial attitudes of Parmenides, shifting the reasoning plan: from how thought can be directed to an object and the qualities of this object to how thought can be directed to the non-existent. Accordingly, the problems of intentionality in the Gorgias’ teaching are considered as well as the privileged status of any of mental states, the nature of word or speech as an autonomous way to develop knowledge about external objects, the issue of meaning as a reference, and inter-subjectivity in cognition. A conclusion is reached that giving preference to one of the paraphrasing versions impoverishes our understanding of the Gorgias’ teaching considerably, while the joint analysis of both versions demonstrates the engagement of the sophistic issues raised by Gorgias, in the philosophical and, particularly, the epistemological paradigm of the ancient as well as modern philosophy.